An Analysis of the Main Characters’ Identity Formation in the Netflix Series Heartstopper Season 1 - Sinaga, Theresia; Purba, Parlindungan; Syahputra, Fikry Prastya (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
The issue of homosexuality and LGBTQ+ themes is growing rapidly in literary works and other media. This research aims to describe the main characters and stages in identity formation in the Netflix series Heartstopper season 1. This research adopts descriptive qualitative methods and focuses on dialogue and scenes by Nick Nelson and Charlie Springs as the main characters. Data collection is done by observation and documentation techniques. The selected data will be analyzed by classifying them into each part of characterization and stage of identity formation, then interpreting them in a narrative form. By using M.J. Murphy's theory, researchers found that there are 8 of 9 methods that reveal the personality of the main characters: personal description, speech, character seen by another, past life, reactions, thoughts, mannerisms, and conversation of others, while there is no direct comment is found. By using Fassinger’s theory, researchers found that Nick went through 4 stages of identity formation: awareness, exploration, deepening, and internalization while Charlie had reached the internalization stage since the beginning of the show. The findings shed light on the characterization as an intrinsic element of literary work and the intricacies of adolescent identity formation, particularly in the context of LGBTQ+ experiences.